SUDDEN DEATH IN HYPERTROPHIC CARDIOMYOPATHY: SEARCH FOR NEW RISK FACTORS - N. S. Krylova; E. A. Kovalevskaya; N. G. Poteshkina; A. E. Demkina; F. M. Khashieva (Российский кардиологический журнал, 2017)
Regardless the developed algorithms for risk stratification in sudden cardiac death (SCD) among patients with hypertrophy cardiomyopathy (HCM) there are SCD cases with no common risk factors. The issue for prediction of SCD in this pathology does not lose its importance.Aim. To study the risk factors for SCD in HCM patients.Material and methods. During 14 years, 198 HCM patients studied (mean age — 60,0±13,8 y.o., 105 males) with ECG, EchoCG, Holter ECG, veloergometry done. During 14 years, 15 died. There was 7 SCD cases with 2 successful resuscitations.Results. In HCM patients there was relation of SCD with the following clinical and instrumental parameters: age (r=-0,19, p=0,015), syncopes in anamnesis (r=0,17, p=0,03), high flow velocity in outflow tract of the left ventricle (LV) in exertion (Ex) (VmaxLVOT) (r=0,3, p=0,04), low Ex tolerance (r=-0,34, p=0,009), abnormal Ex response of blood pressure (ABPR) (r=0,36, p=0,00001), high minimal heart rate (HR) on Holter ECG (r=0,26, p=0,01). Applying the binary logistic regression with inclusion of the most significant predictors, the model was formulated for SCD prediction in HCM patients: SCD=22,28хABPR-6,9хEx Duration+12,5хVmaxLVOT+0,32хMinHR-0,4478хAge-14,7 If the result of equation more than 0 — the patient has high risk of SCD. In negative — SCD risk is minimal. Value of χ2 for the proposed equation is 19,3 (p=0,002).Conclusion. Regardless the common (age, syncopes, severity of LVOT obstruction, ABPR in Ex) there are additional SCD risk factors in HCM patients: low Ex tolerance and high minimal HR on Holter ECG. the mathematic model proposed, making to, based on the age of patient and presence of ABPR in Ex, Ex tolerance, maximal flow velocity in LVOT in Ex, as minimal HR by Holter ECG, to reveal patients with high risk of SCD.